2017
DOI: 10.1016/j.cobeha.2017.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Mixed emotions within the context of goal pursuit

Abstract: Development in adulthood occurs through the process of setting and working toward goals. Emotions link experiences to goals and action, and as such are integral to goal setting, evaluation of goal progress, and goal pursuit. When viewed in the context of goals, the simultaneous experience of positive and negative or “mixed” emotions coheres with the complexity of goal pursuit within the context of competing demands in daily life. Mixed emotions may be experienced as uncertainty in which goal to prioritize, amb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 44 publications
(51 reference statements)
2
24
0
Order By: Relevance
“…Research on the psychological functions of nostalgia dovetails with the demonstrated benefits of emotional ambivalence. Ambivalent affect could influence cognitive flexibility (Mejía & Hooker, 2017; Rothman & Melwani, 2017). Ambivalent affect facilitates contradictory appraisals of a situation (e.g., certain and uncertain, under control and not under control).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on the psychological functions of nostalgia dovetails with the demonstrated benefits of emotional ambivalence. Ambivalent affect could influence cognitive flexibility (Mejía & Hooker, 2017; Rothman & Melwani, 2017). Ambivalent affect facilitates contradictory appraisals of a situation (e.g., certain and uncertain, under control and not under control).…”
Section: Discussionmentioning
confidence: 99%
“…Ambivalent affect facilitates contradictory appraisals of a situation (e.g., certain and uncertain, under control and not under control). This, in turn, may activate a wider range of (atypical) information, give awareness to new priorities, and encourage the pursuit of novel options (Mejía & Hooker, 2017; Rothman & Melwani, 2017). Indeed, emotional ambivalence (e.g., recalling an event such as a graduation) fosters creativity (Fong, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The perception of conflict may be a crucial element in the unique experience of ambivalent affective states, distinguishing them from a simple sum of two simultaneous experiences (Berrios, Totterdell, & Kellett, 2015; Mejia & Hooker, 2017; Schulte, Maderwald, Kraemer, & Brand, 2012). Insula and OFC projections to lateral prefrontal and anterior cingulate regions likely contribute to the experience of conflict.…”
Section: Conflict Is Critical To the Function Of Ambivalent Affectmentioning
confidence: 99%
“…However, an alternative view of mixed emotions, which we term the conflict perspective, suggests that mixed emotions are conflicting and agonizing states (Mejía & Hooker, 2017;van Harreveld et al, 2009) that are linked to negative traits, negative life events, and negative emotionality (Barford et al, 2020;Barford & Smillie, 2016;Hui et al, 2009). Indeed, some evidence suggests that mixed emotions could be linked to motivational and behavioral avoidance (Durso et al, 2016;van Harreveld et al, 2015) and could have negative implications for self-esteem and well-being (Newman et al, 2019).…”
mentioning
confidence: 99%